(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
هدفت هذه الدراسة التعرف إلى الصعوبات التي تعيق استخدام شبكة الانترنت لدى طلبة الجامعة الافتراضية السورية. ومعرفة أثر متغيرات: الجنس، التخصص الدراسي، وامتلاك جهاز الحاسوب وتوفر خدمة الانترنت، استخدم لهذا الغرض عينة بلغ حجمها (400) طالب وطالبة منهم (200) طالب و(200) طالبة موزعين إلى برامج تعليمية مختلفة. وقد أظهرت نتائج الدراسة أن أهم الصعوبات التي تعيق استخدام الانترنت هي عدم معرفة الطالب بأهمية الانترنت وعدم معرفته بالهدف من استخدام هذه الخدمة، وقناعته بأن مساوئ هذه الخدمة أكثر من حسناتها, كما كشفت النتائج عن عدم وجود فروق جوهرية بين الجنسين والصعوبات التي تعيق استخدام الانترنت، بينما أظهرت النتائج وجود فروق جوهرية في هذه الصعوبات تعزى إلى متغيرات توفر جهاز الحاسوب وخدمة الانترنت لدى الطالب وذلك لصالح الطلاب الذين تتوفر لديهم أجهزة الحاسوب وخدمة الانترنت. This study aimed to identify the difficulties that hinder the use of Internet among students of the Syrian Virtual University. It also tried to know the impact of variables: gender, academic specialization, owning a computer and provision of Internet service. The study was conducted on a sample of 400 students, 200 male students and 200 female students of educational programs. Results showed that the main difficulties that hinder the use of Internet were the student’s lack of knowledge of the importance of the Internet and aim of its use. Students also believed that the disadvantages of this service were more than its advantages. Results did not show gender-based significant differences; however, there were significant differences in these difficulties attributed to variables of computer ownership and availability of Internet service in favour of students who have the computers and Internet service.